Climate change criminology - White, R. D. (Robert Douglas), 1956- (New horizons in criminology., 2018)
Leading green criminologist Rob White asks what can be learned from the problem-solving focus of crime prevention to help face the challenges of climate change. Part of the New Horizons in Criminology series.